Spinal cord injury in natural disasters - O'Connell, Colleen (Henry Stewart Talks, 2012)
Disaster and spinal cord injury (SCI), Persons with existing SCI in disaster zones, Co-ordination and mobilization, Expertise, Survey and assessment, Regional capacity, Haiti 2010, Acute care, Acute care challenges: ISCOS summary, Field hospital critical needs, Best practice guidelines on surgical response, Rehabilitation, Health maintenance, Adapting to local needs, Equipment, Community reintegration, Post disaster considerations, Planning for the next disaster